If the equation is -3x^2+6x-4 then the vertex is (1,-1)
Answer:
x-2x = -3 and x = 3
Step-by-step explanation:
Given the expression
y=x+5.... 1
y-2x=2.... 2
Substituting the first equation into the second we will have;
From 2;
y -2x = 2
x+5-2x = 2
x-2x +5 = 2
x-2x = 2-5
x-2x = -3
-x =-3
x =3
Hence the required equation is x-2x = -3 and x = 3
Answer:
3 2/3
Step-by-step explanation:
To do this question, you would need to multiply 7 1/3 with 1/2. The answer is 3 2/3.
Answer:
What are you talking about?
Step-by-step explanation: